Maximum Carboxylation Rate Estimation With Chlorophyll Content as a Proxy of Rubisco Content. Issue 8 (1st August 2020) - Lu, Xuehe; Ju, Weimin; Li, Jing; Croft, Holly; Chen, Jing M.; Luo, Yiqi; Yu, Hua; Hu, Haijing
Abstract: The maximum carboxylation rate (Vcmax) is a key parameter in determining the plant photosynthesis rate per unit leaf area. However, most terrestrial biosphere models currently treat Vcmax as constants changing only with plant functional types, leading to large uncertainties in modeled carbon fluxes. Vcmax is tightly linked with Ribulose‐1, 5‐bisphosphate carboxylase/oxygenase (Rubisco). Here we investigated the relationship between leaf chlorophyll and Rubisco (Chl‐Rub) contents within a winter wheat paddock. With chlorophyll as a proxy of Rubisco, a semimechanistic model was developed to model Vcmax25 (Vcmax normalized to 25°C). The Chl‐Rub relationship was validated using measurements in a temperate mixed deciduous forest in Canada. The results showed that Rubisco was strongly correlated with chlorophyll ( R 2 = 0.96, p < 0.001) for winter wheat since the absorption of light energy by chlorophyll and the amount of CO2 catalyzed by Rubisco are tightly coupled. Incorporating the Chl‐Rub relationship into the semimechanistic model, the root mean square error of modeled Vcmax25 was the lowest among all estimation models. The slopes of Chl‐Rub relations were almost consistent in the winter wheat and temperate forest, demonstrating the potential for using leaf chlorophyll content as a proxy of leaf Rubisco in modeling Vcmax25 at large spatial scales. We anticipate that improving Vcmax25 estimates over time and space will reduce uncertainties in global carbon budgets simulated by terrestrial biosphere models. Key Points: Similar linear chlorophyll‐Rubisco relationships were found between two vegetation types Estimation of Vcmax25 was improved when considering chlorophyll‐Rubisco relationship The potential of mapping Vcmax25 with chlorophyll content was demonstrated